FUNGSI PERTUNJUKAN WAYANG KULIT LAKON TIRTA PERWITASARI: PERSPEKTIF ALAN DUNDES - Madah Chaulah Fitriyah; Eko Cahyo Prawoto (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the functions of the Tirta Perwitasari wayang kulit performance by Ki Cahyo Kuntadi based on Alan Dundes’ theory. The research employs a qualitative descriptive method, using data sourced from a recorded performance uploaded on YouTube. The data, consisting of utterances, songs (tembang), and dialogues, were analyzed through transcription, translation, and functional classification. The analytical techniques include data identification, interpretation, and conclusion drawing. The results indicate that this performance serves five main functions: as an educational tool, a means of strengthening solidarity, a social control mechanism, a medium for criticism, and a source of entertainment and consolation. This study emphasizes that wayang kulit is not merely a form of entertainment but also plays a crucial role in conveying life values to society.